Guidance for the provision of antenatal services during the COVID-19 pandemic. (2nd May 2020) - Richens, Yana; Wilkinson, Meg; Connor, David
Abstract : Novel coronavirus, known as severe acute respiratory syndrome coronavirus 2 (SARS-COV-2), is a new strain of coronavirus causing the COVID-19 infection. The incubation period is estimated at 0–14 days (mean 5–6 days). The majority of people with COVID-19 infection have mild symptoms. Typical symptoms include a fever and cough which may progress to a severe pneumonia causing breathing difficulties. Severe symptoms are more likely in people with weakened immune systems, older people and people with long-term conditions. Pregnant women do not appear to be more susceptible to the consequences of an infection with COVID-19 than the general population. Special consideration should be given to pregnant women with concomitant medical illnesses. There is currently no evidence concerning transmission through genital fluids or breastmilk.